Molecular epidemiology, antimicrobial susceptibility, and pulsed-field gel electrophoresis genotyping of Pseudomonas aeruginosa isolates from mink - Zhao, Yongda (Can J Vet Res, 2018)
Pseudomonas aeruginosa is an important animal pathogen and contributes to hemorrhagic pneumonia in mink. Between April 2011 and December 2016, samples of lung, liver, and spleen were collected from mink with this disease on 11 mink farms in 5 Chinese provinces. From these samples, we obtained 98 isolates of P. aeruginosa that belonged to 5 serotypes: G (n = 58), I (n = 15), C (n = 8), M (n = 5), and B (n = 2); 10 isolates were not typeable (10/98). More than 90% of the isolates formed biofilms, and 85% produced slime. All 98 isolates were resistant to 10 antibiotics (oxacillin, ampicillin, penicillin G, amoxicillin, ceftriaxone, cefazolin, cefaclor, tilmicosin, tildipirosin, and sulfonamide). However, almost all were susceptible to gentamicin, polymyxin B, and amikacin. We identified 56 unique genotypes by pulsed-field gel electrophoresis. These findings have revealed genetic diversity and high antimicrobial resistance in P. aeruginosa isolated from mink with hemorrhagic pneumonia and will facilitate the prevention and control of this disease.